2014
DOI: 10.5812/ircmj.16729
|View full text |Cite
|
Sign up to set email alerts
|

Penile Length and Anogenital Distance in Male Newborns From Different Iranian Ethnicities in Golestan Province

Abstract: Background:Anogenital distance (AGD) is a feasible and accepted parameter of exogenous or endogenous androgens effects on development of reproductive system.Objectives:Since there is no report on penile length (PL) and AGD in our region, we investigated these parameters in male newborns in Golestan Province, Iran.Patients and Methods:In this cross-sectional study, we measured stretched PL and AGD in term newborns from different races in Dezyani Gynecologic Hospital of Gorgan, Iran. We also recorded the anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…Thus, there is a growing body of literature on AGD and its correlates in humans, reflecting the importance of this measure. Normative data for AGD during infancy have been published for some populations, but these may not be applicable to our population in Ghana since ethnic/racial differences have been reported [7, 10, 21]. To the best of our knowledge, no such studies have been carried out in Ghana.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Thus, there is a growing body of literature on AGD and its correlates in humans, reflecting the importance of this measure. Normative data for AGD during infancy have been published for some populations, but these may not be applicable to our population in Ghana since ethnic/racial differences have been reported [7, 10, 21]. To the best of our knowledge, no such studies have been carried out in Ghana.…”
Section: Introductionmentioning
confidence: 82%
“…The lack of significant association of AGD with gestational age in our study was not unexpected as all the babies were full term. Race/ethnicity may also play a role in AGD differences across studies, and indeed Alaee et al [21], Phillip et al [7], and Papadopoulou et al [10] all reported racial/tribal differences in AGD. We found AGD1, AGD2, and AC to be significantly different by maternal tribe, but the limited number of babies from certain tribes (Ga-Adangbe and Ewe) forestalled further meaningful analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies of AGD in boys measured AS, but in six studies, AP measurements were also included (Romano-Riquer et al, 2007; Sathyanarayana et al, 2010; Ozkan et al, 2011; Papadopoulou et al, 2013a; Alaee et al, 2014; Park et al, 2015). The mean (± SD) of 26.8 ± 3.1 mm in VHEMBE boys at birth was somewhat longer than that reported from Cambridge, England 19.6 ± 6.1 mm (Thankamony et al, 2009); Morelos, Mexico 21.0 ± 3.0 (Salazar-Martinez et al, 2004); Tapachula, Mexico median = 19.1 mm [Romano-Riquer et al (2007)]; Seattle, USA 23.0 ± 3.8 mm (Sathyanarayana et al (2010)]; Turkey 23.0 ± 0.6 mm (Ozkan et al, 2011); Spain 24.7 ± 5.1 mm (Papadopoulou et al, 2013a); Iran 24.5 ± 2.5 mm (Alaee et al, 2014); and Korea 23.0 ± 0.2 mm in normal birth weight new borns (Park et al, 2015), but shorter than reported from Nigeria 31.11 ± 0.64 mm (Avidime et al, 2011), and similar to that reported from Crete 27.1 ± 4.4 mm (Papadopoulou et al, 2013a) (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Error bars represent the standard deviation. Data obtained from Salazar-Martinez et al, 2004; (Mexico), Sathyanarayana et al, 2010; (Seattle), Ozkan et al, 2011; (Turkey), Papadopoulou et al, 2013a; (Spain and Crete), Thankamony et al, 2009; (England), Avidime et al, 2011; (Nigeria), Alaee et al, 2014; (Iran), and Park et al, 2015; (Korea).…”
Section: Figurementioning
confidence: 99%
“…Early recognition of penis size abnormalities is important as it might be the first sign of congenital or endocrine disorders like growth hormone deficiency or hypopituitarism or other disorders of sexual differentiation 1 . Penis length (PL) is reported to vary between different races and ethnici ties [2][3][4][5] . This makes it necessary to establish standard values for penile sizes in healthy neonates in each country.…”
mentioning
confidence: 99%